The Change Building Blocks Toward Sustainable Organizations: Learning From Three Sectors - Sudirman Said; Aurik Gustomo; Yudo Anggoro (Jurnal Organisasi dan Manajemen, 2023)
Purpose - This research aims to identify processes and stages in managing sustainable change so that organizations are able to survive in different dynamic conditions, as all organizations (public, private and non-profit) are continuously forced to change to stay competitive in the society. The ability of the leaders of organization to strategically determine the direction of changes and manage change are the fundamental skills. Methodology - This research is qualitative research using multiple-case study that carried out in six organizational settings within three different sectors. Data were collected in 2021, from archival reviews and semi-structured interviews with eighteen change leaders, from six organizations. The data coded and analyzed using NVIVO to find out the common pattern on how the leaders managing changes in three sectors. Findings - The research identify five common building blocks of change: identifying rooms for improvement, organizing change agents, mobilizing support, executing change, and sustaining the change results. Originality - Leadership development is identified as the most effective strategies for sustaining change and transformation initiatives in all three sectors. As this research is conducted in Indonesian institutional setting, the further studies are needed to investigate whether the five building blocks of change are universally applicable.